DIY Dreams and the Potential of Home. Issue 1 (2nd January 2019) - Mackay, Michael; Perkins, Harvey C.
Abstract: Despite the cultural and economic importance of do-it-yourself (DIY) home improvement, questions about its role in the production and consumption of home have been traversed in only a limited way in the housing studies literature. We consider New Zealanders' DIY house improvement intentions and what these ideas for house modification reveal about the idealized relationships they have with their dwellings. We focus on homeowners' thinking and dreaming about the ways the material and symbolic "potential" of home can be achieved by engaging in DIY projects. We theorize our work using the literatures on house and home, self-provisioning activities, leisure work and cultural intermediation, particularly the important roles played by family, friends and print and electronic media in advancing ideas for DIY projects.